The Explanatory Study of Grammar Skill for Primary Student (in Term of Locus of Control and Teaching Model) - Yuda, Yefta Elia; Hadiwijaya, Munawwir (UIBU, 2022)
English grammar plays a crucial role in developing writing and speaking skills at the elementary school level. However, students’ grammar mastery varies according to psychological and pedagogical factors that shape their learning engagement. This study aims to analyze the influence of locus of control and learning models on the grammar skills of elementary school students, as well as to examine the moderating role of external locus of control. The research employed a quantitative approach involving 120 students in grades 4–6 at SD Kristen Aletheia Malang. Data were collected using validated and reliable questionnaires and analyzed using Moderated Regression Analysis (MRA). The results show that internal locus of control has a significant positive effect on grammar skills, indicating that students who believe in their own effort tend to achieve better grammar performance. Learning models were also found to significantly enhance students’ grammar ability through increased engagement and structured practice. Furthermore, external locus of control significantly moderated the relationship between learning models and grammar skills, suggesting that students who rely on external reinforcement benefit more from supportive instructional strategies. These findings highlight the importance of considering both student psychological characteristics and appropriate learning models to optimize English learning outcomes in primary education.